2020
DOI: 10.1002/bse.2478
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation practices enhancing corporate environmental performance via knowledge creation: Does environmental management system implementation matter?

Abstract: The academic literature on environmental management has provided extensive insights into the determinants of corporate environmental performance. However, few empirical studies have explored whether and how three core components of corporate market orientation (i.e., customer orientation, competitor orientation, and interfunctional coordination) affect environmental performance. Building on institutional theory and the absorptive capacity perspective, this study investigates the relationships among market orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 199 publications
1
63
0
3
Order By: Relevance
“…Organizations are under pressures to make their operations environmentally sustainable by adopting circular economy (CE) principle and logic (Linder & Williander, 2017), with the direction and support from government, by collaborating with upstream and downstream organizations (MacArthur, 2014(MacArthur, , 2013. Many organizations are also adopting environmental management system (EMS) to improve quality, reduce manufacturing cost, reduce carbon footprints, and thereby enhance reputational capital among peer groups (Jiang, Rosati, Chai, & Feng, 2020;MacArthur, 2014;Murray, Skene, & Haynes, 2017) and gain social legitimacy. CE aims at reducing solid waste, landfill and emissions, which are environmental challenges through activities such as reuse, remanufacturing and/or recycling (Murray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Organizations are under pressures to make their operations environmentally sustainable by adopting circular economy (CE) principle and logic (Linder & Williander, 2017), with the direction and support from government, by collaborating with upstream and downstream organizations (MacArthur, 2014(MacArthur, , 2013. Many organizations are also adopting environmental management system (EMS) to improve quality, reduce manufacturing cost, reduce carbon footprints, and thereby enhance reputational capital among peer groups (Jiang, Rosati, Chai, & Feng, 2020;MacArthur, 2014;Murray, Skene, & Haynes, 2017) and gain social legitimacy. CE aims at reducing solid waste, landfill and emissions, which are environmental challenges through activities such as reuse, remanufacturing and/or recycling (Murray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, PESs have become increasingly important in China (Jiang et al, 2020;Wang et al, 2018). Moreover, we conducted a summary independent-samples t-test to compare the means of green management practices in our sample with those in recent studies such as Jiang et al (2020), but no significant differences were found. These results suggest that our measure is valid and our data could offer insights similar to those provided in the more recent studies.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 87%
“…From the practice view, as environment deterioration remains as a top concern in China and consumers and stakeholders exhibit rising expectations for green products and services, environmental responsibility becomes a source of competitive advantage and a driver of long-term success (Lee et al, 2018;Li et al, 2020). Hence, PESs have become increasingly important in China (Jiang et al, 2020;Wang et al, 2018). Moreover, we conducted a summary independent-samples t-test to compare the means of green management practices in our sample with those in recent studies such as Jiang et al (2020), but no significant differences were found.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…EMS is voluntarily adopted, and it has been proven to be a critical factor in the success of firms that seek to balance their finance and sustainability aspects (Bravi et al , 2020). One empirical study found that EMS implementation can assist managers who want to please the expectations of stakeholders (Jiang et al , 2020). Regardless of the size of firms, resource allocation is done to obtain the desired results and benefits from EMS.…”
Section: The Theoretical Backgroundmentioning
confidence: 99%
“…As such, businesses are moving away from harming the environment and voluntarily embracing environmental management systems (EMS) (Kim and Park, 2017; Salim et al , 2018; Khan et al , 2021). EMS such as ISO14001 allows firms to strike the right balance between their goal of making profits, paying dividends to shareholders and also recognizing their ethical responsibilities to be sustainable and environmentally friendly for the sake of future generations (Feng and Wang, 2016; Jiang et al , 2020; Seifert and Guenther, 2020; Voinea et al , 2020). Over time, the managers of such firms have realized that implementing EMS can be successful if employees are involved in a meaningful way (Ansari et al , 2020; Yuriev et al , 2018).…”
Section: Introductionmentioning
confidence: 99%